ANALISIS EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA AGRIBISNIS PETERNAKAN PT INKUD SATWA NUSANTARA JAKARTA - Ridwan Lutfiadi (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
This research was conducted to know how efficiently the Inkud Satwa Nusantara runs the business operation of feedlotting, in the line with the current situation of monetary crisis in Idonesia. Cobb-Douglas ’s Function of Production was used to determine efficiency value in utilizing production inputs. The reseacrh concluded that in the situation of decreasing returns to scale, the efficiency in utilizing of concentrates (grain feed) and forages have been made. fVhile, partially, for overhead cost and labor was not efficient yet.